Theoretical Perspectives on Human Rights and Literature. - Goldberg, Elizabeth Swanson, 1966- (Routledge interdisciplinary perspectives on literature., 2011)
What can literary theory reveal about discourses and practices of human rights, and how can human rights frameworks help to make sense of literature? How have human rights concerns shaped the literary marketplace, and how can literature impact human rights concerns? Essays in this volume theorize how both literature and reading literarily can shape understanding of human rights in productive ways. Contributors to Theoretical Perspectives on Human Rights and Literature provide a shared history of modern literature and rights; theorize how trauma, ethics, subjectivity, and witnessing shape repre.